2022
DOI: 10.7759/cureus.21112
|View full text |Cite
|
Sign up to set email alerts
|

Acanthamoeba Keratitis: A Single-Institution Series of Four Cases With Literature Review

Abstract: Acanthamoeba species are free-living protozoa found pervasively in water and soil, which can cause infections of the central nervous system, skin, and eye. Amoebic keratitis (AK) is a vision-threatening, often chronic infection that is associated with the use of soft contact lenses due to corneal microtrauma and improper cleaning and storage. Although AK infections are rare, they cause significant morbidity including vision loss due to the diagnostic and therapeutic challenges they pose.The clinical course is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…A further study used IVCM in three of their four patients diagnosed with AK, which showed worsening symptoms despite treatment. In these three cases, IVCM demonstrated cysts which had migrated deeper into the cornea, and a deep anterior lamellar keratoplasty was necessary in all three cases 63 …”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations
“…A further study used IVCM in three of their four patients diagnosed with AK, which showed worsening symptoms despite treatment. In these three cases, IVCM demonstrated cysts which had migrated deeper into the cornea, and a deep anterior lamellar keratoplasty was necessary in all three cases 63 …”
Section: Resultsmentioning
confidence: 85%
“…A total of 13 studies reported the use of IVCM to track AK during and/or after treatment 9,30,34,39,42,46–48,53,55,59,63,64 . Two described the appearance of cysts and trophozoites following treatment 34,42 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the pathogens that can cause keratitis in coastal communities with the majority of work as divers and fishermen is Acanthamoeba spp. Acanthamoeba parasites can cause progressive infection of the cornea 8 . The main risk factor for Acanthamoeba (KA) is the use of contact lenses while swimming or diving.…”
Section: Introductionmentioning
confidence: 99%